verify the following
Attachments:
![](https://hi-static.z-dn.net/files/dc4/c0ac6b3d3c13446f668821ad216f555f.jpg)
Answers
Answered by
4
heya...
your answer is:
6^5×6^4 = 6^9 ( a^m×a^n = a^m+n)
6^5+4 = 6^9
It may help you...☺☺
your answer is:
6^5×6^4 = 6^9 ( a^m×a^n = a^m+n)
6^5+4 = 6^9
It may help you...☺☺
Answered by
0
The base of exponent is same, so
![5 + 4 = 9 5 + 4 = 9](https://tex.z-dn.net/?f=5+%2B+4+%3D+9)
Hence; 6 to the power 5 multiplied by 6 to the power 9 is equal to 6 to the power 9.
__________________________________
__________________________________
Hope it helps
__________________________________
Don't forget to mark me as brainlist.
Hence; 6 to the power 5 multiplied by 6 to the power 9 is equal to 6 to the power 9.
__________________________________
__________________________________
Hope it helps
__________________________________
Don't forget to mark me as brainlist.
aStusent:
Please mark me as brainlist
Similar questions